Network disruption detected in BF (Burkina Faso) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Burkina Faso. Data sourced from IODA.
Network Disruption Incident ID: BF-2026-0002. Severity: critical. Confidence: 70%